Parametric investigation of heat transfer enhancement and pressure loss in louvered fins with longitudinal vortex generators - Dezan, Daniel Jonas; Yanagihara, Jurandir Itizo; Jenovencio, Guilherme; Salviano, Leandro Oliveira [UNESP] (Elsevier B.V., 2019)
The present work aims to perform a parametric study of heat transfer enhancement and the associated pressure loss applied to louvered fins with rectangular winglet vortex generators (RWL). The contributions of a set of design variables on heat transfer and pressure drop are evaluated for two geometry types, L1 and L2. The procedure to investigate the relative importance of the geometrical design variables on thermal-hydraulic performance is enabled by a Design of Simulations (DOS) method called Latin Hypercube Sampling (LHS) in association with a modern non-parametric statistical method (Smoothing Spline ANOVA method) and Computational Fluid Dynamics. Outcomes from the screening analyses turned out that the louver angle is the unique contributor to friction factor for both geometry types and this behaviour is independent of Reynolds number. With respect to heat transfer, the contributions of the input variables are different for both geometry types and Reynolds numbers. For Re-Dh = 120, no important two-factor interaction effects were observed for both L1 and L2, in the same way as occurred in terms of friction factor. Conversely, for Re-Dh = 240 one relevant interaction effect was observed.
Keywords: Louvered fin; Longitudinal vortex generators; Heat transfer enhancement; Screening analysis; Smoothing spline ANOVA method; Computational fluid dynamics; Thermal-hydraulic performance